Enhancement of zakat distribution management system: case study in Malaysia - Lubis, Muharman; Yaacob, Nurul Ibtisam; Omar, Yusoff; Ahmad Dahlan, Abdul Rahman (University Sultan Zainal Abidin, 2011)
Zakat is the pivot approach in Islamic teachings to encounter social problem such as poverty in society by sharing the percentage of wealth to relevant recipients as the obligation to the person who affordable. This study attempts to investigate the suitable system based on technology perspective to develop the effective and efficient zakat management process at national level in the beginning and international level further with addressing Malaysia issues that focuses in distribution process. Practically, the management of zakat has some issues that need much attention, which based on the findings of previous study indicated high percentage of zakat recipients also zakat payers are not satisfied with the management process. Interestingly, zakat recipients increase almost each year gradually while the high percentage around 15 % of zakat becomes undistributed every year. This phenomenon depicts to Malaysian society that zakat distribution performance does not have good performance contradict with zakat collection that grow averagely each year. The integrated approach by using Geographical Information System concepts is proposed that hopefully, it will enhance the capability in statistical analysis result and distribution analysis characteristic for improvement in zakat management between states internally and externally.